Dynamique sémiotique… et « anthropologie langagière » : une perspective (contrepoint « phénoménologique ») (Signifiances (Signifying), 2021)
Taking as support five themes specific to semiotic dynamics: either the experiential subject and naturalness, the splitting, the historicity and its retention, the WE and finally the perspective of the Möbius strip and the helicoidal drift which sutures the splitting and tends to send us back with ourselves in a single plane from which we do not come out, it will be a question of wondering about the potential for meeting with other research traditions from the philosophical order, especially phenomenological (Merleau-Ponty, …); and therefore to compare, if not enter into resonance, this semiotic dynamics with other conceptualizations which do not identify with it and do not cover it, but which no doubt cross it. Therefore, the confrontation of certain points of conceptualization and certain displayed objectives can only be enriching.